Use of modal interference approach (MIA) to reduce wind-induced building motions. (15th May 2018) - Xie, Jiming; Borysiuk, D.
Highlights: A structural optimization for wind effects by making use of modal interference. Principles and application procedures of the proposed modal interference approach. Effectiveness validation of MIA by using wind tunnel model tests. Benefits and limitations of using MIA for super-tall building design. Abstract: A new method of structural optimization to reduce across-wind responses of tall buildings, named MIA (modal interference approach), is proposed in this paper. This method is based on an observation that if there are multiple modes participating in vortex-induced oscillations, these modes tend to interrupt each other, resulting in considerably smaller amplitude of vibration in comparison with a single mode response. A theoretical analysis was performed to describe this phenomenon, based on which MIA was developed. The new method is to stimulate multi-mode responses to vortex excitations by rotating the modal directions away from the wind-susceptible building directions and separating the frequencies between the participated modes. Wind tunnel studies of a high-frequency force balance model and a stick aeroelastic model verified the effectiveness of the proposed method.